2022
DOI: 10.1097/gox.0000000000004543
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Fat Grafting: Evaluation of Efficacy in Pain Relief

Abstract: Introduction: Autologous fat grafting (AFG) has been used in reconstructive plastic surgery for over a century. Although it has obvious benefits to the aesthetic appearance of many reconstructive surgeries, less appreciated advantages of fat grafting have also been shown in potential pain reduction. This can be seen across the board from head to toe with examples ranging from facial nerve injury to pedal atrophy and foot ulcers. The purpose of this literature review is to evaluate the efficacy of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…With an increased focus on the effect of fat grafting in recent years as a potential regimen for treating PMPS, there is a growing number of promising new evidence and research articles regarding this topic. While two previous systematic reviews have found a reduction in pain following fat grafting after mastectomy, these reviews may have limited power, as they included three and six studies, respectively [8,10]. Furthermore, neither review performed a meta-analysis nor examined complication rates associated with fat grafting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With an increased focus on the effect of fat grafting in recent years as a potential regimen for treating PMPS, there is a growing number of promising new evidence and research articles regarding this topic. While two previous systematic reviews have found a reduction in pain following fat grafting after mastectomy, these reviews may have limited power, as they included three and six studies, respectively [8,10]. Furthermore, neither review performed a meta-analysis nor examined complication rates associated with fat grafting.…”
Section: Introductionmentioning
confidence: 99%
“…However, there remains no standard treatment or recognized clinical guidelines for PMPS [8]. Botulinum toxin, neuromodulation, regional anesthesia, oral analgesia, and injection therapy have provided only temporary relief [9,10]. Autologous fat grafting, a procedure which involves the surgical transfer of adipose tissue from one area of the body to another, is a well-established technique in the field of reconstructive plastic surgery with uses such as for cosmesis and scar irritation [8].…”
Section: Introductionmentioning
confidence: 99%